1994
DOI: 10.1128/aac.38.10.2238
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of insertion sequence IS257 in dissemination and expression of high- and low-level trimethoprim resistance in staphylococci

Abstract: The transposon-like structure Tn4003 and related elements were found to encode high-and low-level trimethoprim resistance (Tpr) in Staphylococcus aureus and coagulase-negative staphylococci. By using transcriptional fusions in Escherichia coli, the variation in resistance levels was found to correlate with the transcriptional activity of the region presumed to carry the promoter for the operon containing the Tpr dihydrofolate reductase gene, dfrA, encoded by these elements. The reduced transcriptional activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 42 publications
(42 reference statements)
0
35
0
Order By: Relevance
“…Moreover, high-and low-level trimethoprim resistance in Staphylococcus aureus is mediated by genomic deletions adjacent to a copy of IS257 inserted upstream from the dihydrofolate reductase gene, dfrA. In this case, the insertion sequence encodes a Ϫ35 sequence that is necessary for full promoter activity (18). IS6110 can promote gene expression in M. tuberculosis 210 (3).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, high-and low-level trimethoprim resistance in Staphylococcus aureus is mediated by genomic deletions adjacent to a copy of IS257 inserted upstream from the dihydrofolate reductase gene, dfrA. In this case, the insertion sequence encodes a Ϫ35 sequence that is necessary for full promoter activity (18). IS6110 can promote gene expression in M. tuberculosis 210 (3).…”
Section: Methodsmentioning
confidence: 99%
“…7) (15). IS257 has been found to insert into several locations in pT181, with no apparent insertion site specificity (16,25,35).…”
Section: Discussionmentioning
confidence: 99%
“…The canonical promoter consensus is shown at the top. The TSPs mapped for dfrA on pSK1 (15) and tetA(K) on SK1660 (this study) are indicated. Eight-base pair target duplication sequences are denoted by dashed arrows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations